The background and challenges faced by the small medium enterprise: A human resource development perspective - Omar, Siti Sarah; Lawrence, Arokiasamy; Ismail, Maimunah (International Journal of Business and Management, 2009)
In the recent years, a number of emerging issues are posing serious challenges to the small and medium sized enterprises (SME’s) in Malaysia. Hence, these enterprises enter the new era, dramatic challenges begun such as establishing new enterprises, globalization, financial constraints, high turnover, low motivation among employees, lack of human capital building, and more challenges ahead. Thus understanding the problems and challenges are fundamental solutions to expand and strategize SME’s to future progress and grows. Therefore this article examines the background and challenges face by SME’s which play a vital role in the nation growth. The uniqueness of this paper is the emphasis on the human resource development perspective which is important for SME’s to progress and be competitive. Finally, this article maps out how future research can be more sensitive to how SME’s actually develop their own human resource development for future development.